Early-strength nano C-S-H crystal nucleus concrete under low-temperature curing environment and preparation method thereof

By adding nano C-S-H crystal nuclei to concrete under low temperature environments, optimizing material ratio and accelerating hydration reactions, the problem of slow development of concrete strength in low temperature environments is solved, significantly improving early strength, shortening construction cycles and reducing costs .

CN119462013APending Publication Date: 2025-02-18ROAD & BRIDGE INT CO LTD +4
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202411618300.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In low-temperature environments, the development of concrete strength slowly affects the construction progress and structural safety. Traditional early strength agents have problems of long-term strength retracting, easy expansion and poor adaptability. The steam maintenance method has a long construction period, high energy consumption and high cost.

Method used

By adding nano C-S-H crystal nuclei during the concrete preparation process, the material combination and ratio are reasonably designed, the cement hydration reaction is accelerated, and a dense concrete structure is formed, which significantly improves early strength.

Benefits of technology

In low temperature environment, the early strength of concrete is significantly improved. The strength can reach more than 25MPa in one day, the strength can reach more than 35MPa in three days, the strength can reach more than 40MPa in seven days, and the strength can reach 50MPa in the design requirements in 28 days, which solves the traditional method Inadequate, reducing construction cycle and cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119462013A_ABST
    Figure CN119462013A_ABST
Patent Text Reader

Abstract

The invention discloses early-strength nano C-S-H crystal nucleus concrete in a low-temperature curing environment and a preparation method thereof. The concrete is composed of the following substances in parts by weight: 260-300 parts of PO52.5 ordinary Portland cement; 135 to 155 parts of slag; 60 to 70 parts of fly ash; the water-binder ratio is 0.27 to 0.31; the sand ratio is 0.40 to 0.44; the water reducing agent accounts for 1% of the mass of the gel body; the nano C-S-H crystal nucleus accounts for 6%-10% of the mass of the gel body; 1080 to 1210 parts of coarse aggregate; and 770 to 870 parts of fine aggregate. The method comprises the following steps: (1) respectively weighing the cement, the slag and the fly ash according to the parts by weight, putting into a stirrer, and stirring for 1 minute; 2) continuously adding sand and stone into the concrete mixer, and continuously stirring for about 2 minutes; and 3) adding the water, the water reducing agent and the nano C-S-H crystal nucleus into the mixture, and uniformly stirring for 2 minutes. The method effectively solves the problem of slow development of concrete strength in a low-temperature environment, also solves the problems of long construction period and high maintenance cost of a concrete structure in winter, and has obvious engineering significance and relatively strong economic benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of building materials, and more specifically to early-strength nano-CSH crystal nucleus concrete under low-temperature curing environment and a preparation method thereof. The early strength of concrete is significantly improved through the optimization of mix design and preparation method, and can be applied to construction in high-altitude and cold areas in the west. Background Art

[0002] As an important component of building materials, concrete is widely used in various fields of construction engineering. However, during winter construction, due to the low ambient temperature, the strength of concrete develops slowly, which seriously affects the construction progress and structural safety. Therefore, in order to improve the early strength of concrete, early strength agents are generally added or steam curing methods are adopted. Although traditional early strength agents can accelerate the rate of cement hydration reaction and significantly improve its early strength, there are problems such as long-term strength shrinkage, easy expansion and poor adaptability. The use of steam curing methods not only has a long construction period, but also has large energy consumption and high costs. Therefore, the development of a new hydration accelerator that achieves rapid strength development under steam-free curing conditions has important engineering significance for shortening the construction period, reducing engineering costs, and improving the safety of building structures.

[0003] Nano CSH crystal nucleus is a new type of concrete early strength agent. It promotes the hydration reaction by reducing the energy barrier of the hydration reaction of tricalcium hydrate and dicalcium hydrate to generate CSH, accelerates the hardening process of concrete, and effectively improves the early strength of concrete. While accelerating the hydration reaction, the hydration reaction is more thorough, and the chemical composition and structure of the nano CSH crystal nucleus are exactly the same as the product, so the hydration product is more uniform, the hardened cement slurry is denser, and has fewer defects, which does not affect the durability of concrete. However, the current research on nano CSH crystal nucleus early strength agent is mainly the preparation method of CSH gel nano crystal nucleus early strength agent, or the development of early strength of CSH nano crystal nucleus concrete ("Early strength development in concrete using preformed CSH nano crystals", Saikat et al., pp. 117-214, Construction and Building Materials, 2020), but there is still a blank in the research on the early strength of nano CSH crystal nucleus concrete under low temperature curing environment. Summary of the invention

[0004] The purpose of the present invention is to solve the problem of slow concrete strength development under low temperature environment, add nano CSH crystal nuclei in the concrete preparation process, accelerate the hydration reaction process of cement through reasonable material combination and proportion, form dense concrete, significantly improve its early strength, improve the problems of long-term strength shrinkage, easy corrosion of steel bars and complex preparation of traditional early strength agents, reduce the maintenance cost of steam curing method, and shorten the construction period.

[0005] The main physical and chemical indicators of the nano CSH core are shown in Table 1;

[0006] Table 1 Main physical and chemical indicators of nano CSH core

[0007]

[0008] The technical solution of the present invention is as follows:

[0009] On the one hand, the present invention provides an early-strength nano-CSH nucleus concrete under a low-temperature curing environment, which is composed of the following materials in parts by weight:

[0010] PO52.5 ordinary Portland cement 260 to 300 parts; slag 135 to 155 parts; fly ash 60 to 70 parts; water-cement ratio: 0.27 to 0.31; sand ratio: 0.40 to 0.44; water reducer, accounting for 1% of the mass of the cement; nano CSH crystal nucleus, accounting for 6% to 10% of the mass of the cement; coarse aggregate 1080 to 1210 parts; fine aggregate 770 to 870 parts.

[0011] Furthermore, it is composed of the following materials in parts by weight: 280 parts of PO52.5 ordinary Portland cement; 145 parts of slag; 65 parts of fly ash; water-cement ratio: 0.29; sand ratio: 0.42; water reducer, accounting for 1% of the mass of the cement; nano CSH crystal nuclei, accounting for 8% of the mass of the cement; 1145 parts of coarse aggregate; and 820 parts of fine aggregate.

[0012] The coarse aggregate is 5-15 mm continuously graded crushed stone.

[0013] The fine aggregate is river sand with a fineness modulus of 2.7.

[0014] Another aspect of the present invention provides a method for preparing early-strength nano-CSH nucleus concrete under a low-temperature curing environment, comprising the following steps:

[0015] 1) Weigh cement, slag and fly ash according to the ratio and put them into the mixer, and stir for 1 minute;

[0016] 2) Continue to add sand and stone to the concrete mixer and continue mixing for about 2 minutes;

[0017] 3) Add water, water reducing agent and nano CSH crystal nuclei into the above mixture and stir evenly for 2 minutes to prepare the early strength nano CSH crystal nucleus concrete under low temperature curing environment.

[0018] The key to the high strength of the early-strength nano-CSH crystal core concrete under low-temperature curing environment of the present invention lies in the mix design. Nano-CSH crystal cores can significantly accelerate the hydration reaction process of cement, reduce the activation energy of the hydration reaction, promote the rapid generation of hydration products such as CSH gel, and optimize the microstructure of the cement paste to make it more dense, thereby significantly improving the early strength of concrete in a short time. Therefore, by changing the dosage of nano-CSH crystal cores (6-10%), water-cement ratio (0.27-0.31) and sand ratio (0.40-0.44), the mix ratio is optimized to improve the early strength of nano-CSH crystal core concrete.

[0019] In the present invention, the chemically synthesized nano CSH sol nucleation growth agent serves as a nucleation matrix for promoting cement hydration reaction, and has the same chemical structure as cement hydration products. It plays a "nucleation" and "guiding" role in the cement hydration process, so that the cement hydration products can grow rapidly on the surfaces of these CSH sol primary particles, accelerates the formation of CSH sol, and promotes cement hydration reaction. The mechanism of action of the CSH sol nucleation growth agent and the traditional early strength agent and the ultrafine mineral admixture early strength agent is essentially different: the latter is based on improving activity and accelerating chemical reaction as a starting point, so the hydration reaction is not thorough and complete, and there are multiple defects in the material structure. The nano CSH sol nucleation growth agent is based on the mechanism of "nucleation growth", and while accelerating the hydration reaction, the hydration reaction is more thorough.

[0020] The specifications of nano CSH are: CSH nano-crystal core hydration promoter with particle size less than 300nm.

[0021] Technical effects and advantages of the present invention:

[0022] 1) Convenient construction

[0023] When carrying out concrete construction in a low-temperature environment, the use of concrete mixed with nano-CSH crystal nuclei can improve the convenience of construction. Not only is the preparation, transportation and pouring of nano-CSH crystal nucleus concrete basically the same as ordinary concrete, and the operation is convenient, but it can also effectively avoid problems such as prolonged setting time and slow strength development of concrete due to low temperature, greatly improving the flexibility and efficiency of construction.

[0024] 2) Early strength develops rapidly in low temperature environment

[0025] The early-strength nano-CSH crystal nucleus concrete of the present invention has a high early strength under low-temperature curing environment. Under 0°C curing environment, the strength can reach more than 25MPa in 1 day (1d>50%), more than 35MPa in 3 days (3d>70%), more than 40MPa in 7 days (7d>80%), and 50MPa in 28 days as required by the strength design, which is significantly better than ordinary concrete. Compared with concrete with traditional early strength agent, the nano-CSH crystal nucleus concrete of the present invention does not have the problems of poor adaptability, easy expansion and complex preparation.

[0026] 3) Reduce costs

[0027] The early-strength nano-CSH crystal nucleus concrete under low-temperature curing environment of the present invention can achieve an early-strength effect equivalent to steam curing under low-temperature conditions, replace traditional steam curing, shorten the curing cycle, reduce the curing cost, reduce production energy consumption, and meet the requirements of green and low-carbon development. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The setting time and slump result diagram of the early-strength nano-CSH crystal nucleus concrete prepared in Examples 1 to 4 under low-temperature curing conditions;

[0029] Figure 2 This is a graph showing the compressive strength results of the early-strength nano-CSH nucleus concrete prepared in Examples 1 to 4 under low-temperature curing conditions. DETAILED DESCRIPTION

[0030] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] Example 1: The dosage of nano CSH nuclei is 6%, the water-binder ratio is 0.27 and the sand ratio is 0.40; that is, PO52.5 ordinary Portland cement (57% of the mass of the cementitious material, 296.4kg / m 3 ), fly ash (13% of the mass of cementitious materials, 67.6kg / m 3 ), slag (30% of the mass of cementitious materials, 156.0kg / m 3 ), fine aggregate (775.8kg / m 3 ), coarse aggregate (1163.8kg / m 3 )、Nano CSH nuclei (31.2kg / m 3 ), water reducing agent (1% of the mass of cementitious material, 5.2kg / m 3 )、Water(104.0kg / m3 ).

[0032] Preparation of early-strength nano-CSH crystal nucleus concrete under low-temperature curing environment includes the following steps:

[0033] 1) According to the above weight proportions, cement, slag and fly ash are weighed respectively and put into a mixer and stirred for 1 minute;

[0034] 2) Continue to add sand and stone to the concrete mixer and continue mixing for about 2 minutes;

[0035] 3) Add water, water reducing agent and nano CSH crystal nuclei into the above mixture and stir evenly for 2 minutes to prepare the early strength nano CSH crystal nucleus concrete under low temperature curing environment.

[0036] 4). After preparation, the concrete was left at room temperature for one day to allow it to initially harden and set; then after demoulding, the concrete was placed in a low-temperature environment with a temperature of 0°C and a humidity of >95%; the curing time was 1 day, 3 days, 7 days and 28 days respectively, in order to observe and study the performance changes of the concrete at different curing times.

[0037] Example 2: The dosage of nano-CSH nuclei is 8%, the water-cement ratio is 0.31 and the sand ratio is 0.44; that is, PO52.5 ordinary Portland cement (57% of the mass of the cementitious material, 276.0kg / m3), fly ash (13% of the mass of the cementitious material, 62.9kg / m3), slag (30% of the mass of the cementitious material, 145.2kg / m3), fine aggregate (869.2kg / m3), coarse aggregate (1106.3kg / m3), nano-CSH nuclei (38.7kg / m3), water reducer (1% of the mass of the cementitious material, 4.8kg / m3), and water (96.8kg / m3).

[0038] The early-strength nano-CSH nucleus concrete was prepared under low-temperature curing environment, as in Example 1.

[0039] Example 3: The dosage of nano-CSH nuclei is 8%, the water-cement ratio is 0.31 and the sand ratio is 0.40; that is, PO52.5 ordinary Portland cement (57% of the mass of the cementitious material, 258.2kg / m3), fly ash (13% of the mass of the cementitious material, 58.9kg / m3), slag (30% of the mass of the cementitious material, 135.9kg / m3), fine aggregate (802.7kg / m3), coarse aggregate (1204.0kg / m3), nano-CSH nuclei (36.2kg / m3), water reducer (1% of the mass of the cementitious material, 4.5kg / m3), and water (99.6kg / m3).

[0040] The early-strength nano-CSH nucleus concrete was prepared under low-temperature curing environment, as in Example 1.

[0041] Example 4: The dosage of nano CSH nuclei is 10%, the water-binder ratio is 0.27 and the sand ratio is 0.44; that is, PO52.5 ordinary Portland cement (57% of the mass of the cementitious material, 296.4kg / m 3 ), fly ash (13% of the mass of cementitious materials, 67.6kg / m 3 ), slag (30% of the mass of cementitious materials, 156.0kg / m 3 ), fine aggregate (853.4kg / m 3 ), coarse aggregate (1086.2kg / m 3 )、Nano CSH nuclei (52.0kg / m 3 ), water reducing agent (1% of the mass of cementitious material, 5.2kg / m 3 ), water (83.2kg / m 3 ).

[0042] The early-strength nano-CSH nucleus concrete was prepared under low-temperature curing environment, as in Example 1.

[0043] According to GB / T 50080-2016 "Standard for Test Methods for Performance of Ordinary Concrete Mixtures", the setting time and slump of the early-strength nano-CSH nucleus concrete prepared in Examples 1 to 4 under low-temperature curing conditions were tested. The test results are as follows: Figure 1 According to GB / T 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete", the compressive strength test of the early-strength nano-CSH nucleated concrete prepared in Examples 1 to 4 under low-temperature curing environment was carried out. The test results are shown in Figure 2 shown.

[0044] like Figure 1 As shown, the early-strength nano-CSH nucleus concrete prepared in Examples 1 to 4 under low-temperature curing environment has an initial setting time of more than 180 min; a final setting time of more than 5 h, earlier than 10 h; and a slump maintained between 180 and 200 mm, meeting the requirements for concrete engineering construction.

[0045] like Figure 2 As shown, the early-strength nano-CSH nucleated concrete prepared in Examples 1 to 4 under low-temperature curing environment develops rapidly at a curing temperature of 0°C, and the strength can reach more than 25 MPa in 1 day (up to 33.9 MPa in Example 1), more than 35 MPa in 3 days, more than 40 MPa in 7 days (50.4 MPa in Example 4), and the strength reaches the strength design requirement of 50 MPa in 28 days.

[0046] In summary, the early-strength nano-CSH nucleus concrete under low-temperature curing environment of the present invention can significantly improve the early strength of concrete, shorten the construction period, and reduce production costs under low-temperature environment through optimization of mix design and preparation method.

[0047] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. Early-strength nano-CSH nucleus concrete under low-temperature curing environment, characterized by: It is composed of the following materials in parts by weight: PO52.5 ordinary Portland cement 260 to 300 parts; slag 135 to 155 parts; fly ash 60 to 70 parts; water-cement ratio: 0.27 to 0.31; sand ratio: 0.40 to 0.44; water reducer, accounting for 1% of the mass of the cement; nano CSH crystal nucleus, accounting for 6% to 10% of the mass of the cement; coarse aggregate 1080 to 1210 parts; fine aggregate 770 to 870 parts.

2. The early-strength nano-CSH nucleated concrete under low-temperature curing environment according to claim 1, characterized in that: The cement paste is composed of the following materials in parts by weight: 280 parts of PO52.5 ordinary Portland cement; 145 parts of slag; 65 parts of fly ash; water-cement ratio: 0.29; sand ratio: 0.42; water reducer, accounting for 1% of the mass of the cement; nano CSH crystal nucleus, accounting for 8% of the mass of the cement; 1145 parts of coarse aggregate; and 820 parts of fine aggregate.

3. The early-strength nano-CSH nucleated concrete under low-temperature curing environment according to claim 1, characterized in that: The coarse aggregate is 5-15 mm continuously graded crushed stone.

4. The early-strength nano-CSH nucleated concrete under low-temperature curing environment according to claim 1, characterized in that: The fine aggregate is river sand with a fineness modulus of 2.

7.

5. The method for preparing early-strength nano-CSH nucleated concrete under low-temperature curing environment according to any one of claims 1 to 4, characterized in that: The following steps are involved: 1) Weigh cement, slag and fly ash according to the ratio and put them into the mixer, and stir for 1 minute; 2) Continue to add sand and stone to the concrete mixer and continue mixing for about 2 minutes; 3) Add water, water reducing agent and nano CSH crystal nuclei into the above mixture and stir evenly for 2 minutes to prepare the early strength nano CSH crystal nucleus concrete under low temperature curing environment.

6. The method for preparing early-strength nano-CSH nucleus concrete under low-temperature curing environment according to claim 5, characterized in that: After preparation, the concrete is left to stand at room temperature for one day to allow it to initially harden and set; then after demolding, the concrete is placed in a low-temperature environment with a temperature of 0°C and a humidity of >95%; the curing time is 1 day, 3 days, 7 days and 28 days respectively, in order to observe and study the performance changes of concrete at different curing times.

Citation Information

Cited By

  • ECC for early-strength and high-strength tunnel repair and preparation method thereof

    CN121225949A

  • Quick-setting and quick-hardening concrete and preparation method thereof

    CN121377687A

  • Fast-setting and fast-hardening concrete and method for producing the same

    CN121377687B

  • Fly ash-based cementing material and preparation method thereof

    CN121609541A